Coordinated TSO-DSO operational planning for congestion management in day-ahead and real-time markets - Ali Esmaeel Nezhad; Toktam Tavakkoli Sabour; Ravindra P. Joshi (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
This paper presents a coordinated operational planning approach for handling congestion management in transmission and distribution networks. The developed model is based on a two-stage operational planning process consisting of day-ahead (DA) and real-time (RT) markets. In this regard, both the transmission system operator (TSO) and distribution system operator (DSO) effectively participate in handling the network operation bottlenecks. The performance of the model to address congestion management in centralized and decentralized energy balance markets has been demonstrated to highlight the importance of the coordinated model. The simulation results underscore the functionality and performance of the coordinated TSO-DSO model in alleviating the congestion in real-time markets by implementing upward and downward flexibility as an alternative ancillary service that can be provided by both dispatchable generators and responsive loads at each sector.